Land Law Conceptualization: Realizing an Effective Dispute Resolution Model in Indonesia - Buana, Andika Prawira; Raja, Aksara Alif; Aswari, Aan; Nur Fuady, Muhammad Ikram; Ramadani, Rizki (Jurnal Media Hukum, 2025)
Land dispute resolution in Indonesia is often complex due to procedural inefficiencies and overlapping jurisdictions. Currently, the National Land agency (BPN) functions as a mediator, providing clarifications to the included parties. Dispute resolution by the parties in litigation results in unresolved disputes, resulting in a backlog of cases in court. Therefore, this research aims to re-evaluate the role of the BPN as a mediator and to propose a conceptual framework for an effective resolution model for land disputes. This research uses a juridical-normative process of finding a legal rule to answer the legal issue being researched. The results show that BPN mediation efforts have not sufficiently addressed land disputes due to the non-binding nature. The role of the BPN should be enhanced as an arbitration body under the regulations governing Arbitration and Alternative Dispute Resolution. By serving as arbitrator, the Land Agency can render final and binding decisions without the necessity of undergoing the stages of appeal, cassation, or judicial review, particularly in civil and administrative disputes. Furthermore, this research advocates for the revision of the Notarial Sale and Purchase Agreement to incorporate arbitration provisions and recommends establishing specialized land courts, drawing lessons from existing models in Australia and South Africa.